Production and characterization of tissue engineering scaffolds based on polyhydroxybutyrate-co-hydroxyvalerate polymers - Naznin, Sultana (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/